Sensory screening as a readiness tool for equine-based sport participation in children with autism - Adenan, Fatin Aqilanajwa; Abdul Rahman, Ahmad Fadly (Journal of Islamic, Social, Economics and Development, 2025)
Equine-based sports activities are increasingly recognised as an inclusive physical activity option for children with autism spectrum disorder (ASD), offering opportunities for movement, balance, coordination, and social engagement. However, participation in equine-based sports requires careful consideration of safety and readiness due to the sensory sensitivities commonly observed in ASD and the responsive nature of horses. Although norm-referenced sensory pre-assessment standards for equine activity participation have been established, limited literature has examined how these standards can be applied practically to support sport participation readiness and programme planning. This paper describes the application of a sensory readiness screening framework to support safe participation decisions for equine-based sports activities among children with ASD. The screening focuses on tactile, vestibular, proprioceptive, and auditory perception which are sensory domains closely related to balance control, body awareness, equipment tolerance, and sound reactivity during sport participation. Threshold values adopted from previously published norm-referenced standards are translated into practical readiness categories. The applied framework supports consistent decision-making, individualised sport activity planning, and safer participation in equine-based sports contexts.